2020
DOI: 10.3390/polym12051039
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Fir Wood by Poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) Treatment: Study of Surface and Mechanical Characteristics

Abstract: The ability of poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) (PVBVA) to consolidate Fir wood was studied in terms of the surface and mechanical properties’ changes. Two variables were considered to treat the wood: (i) the concentration (5 and 10 wt.%) of PVBVA solutions and (ii) the method of application (brushing and immersion). The presence of PVBVA on the wood surfaces was confirmed by infrared spectroscopy. Surface roughness measured by optical profilometry did not reveal changes in the topography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…This was supported by the OM results, which showed a thicker layer of polymer on the surface of the wood treated by brushing. A possible explanation for the presence of the thicker layer of polymer on the wood surface could be related to the high solvent evaporation rate when the brushing method was used to coat the wood [53]. This may impede the penetration of the polymer into the wood microstructure, thus obtaining a thicker layer of polymer that, when applied to the wood surface, will protect the wooden material, providing a durable surface that helps to prevent damage and keeps it in good condition.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by the OM results, which showed a thicker layer of polymer on the surface of the wood treated by brushing. A possible explanation for the presence of the thicker layer of polymer on the wood surface could be related to the high solvent evaporation rate when the brushing method was used to coat the wood [53]. This may impede the penetration of the polymer into the wood microstructure, thus obtaining a thicker layer of polymer that, when applied to the wood surface, will protect the wooden material, providing a durable surface that helps to prevent damage and keeps it in good condition.…”
Section: Discussionmentioning
confidence: 99%
“…Another way to protect wood by surface impregnation is to simply insert protective agents slightly under its surface. Harandi et al brushed 5% and 10% solutions of poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) (PVBVA) on silver fir to improve its mechanical properties [238]. They found that both solutions increased the water contact angle to 90%, reaching hydrophobicity, and improved the modulus of rupture (MOR), modulus of elasticity (MOE), plastic hardness and Martens hardness of the treated specimens.…”
Section: Wood Surface Impregnationmentioning
confidence: 99%
“…Accordingly, these coating methods must allow for working in large batches in order to keep a good production rate. Brushing and dipping were also used to perform the surface impregnation of different protective agents into wood substrates, with similar limitations [238][239][240][241]244,246,247]. A quite different, yet interesting method was presented by Volokitin et al, who modified pine and birch with a thermal plasma to produce only a layer of thermo-modified wood [193].…”
Section: Economical Aspectsmentioning
confidence: 99%
“…However, in many situations, the use of original natural material is not economically profitable due to its low abundance in nature or the difficulties of extracting or processing it. Therefore, consolidants have been extensively used for the consolidation of degraded artefacts [ 5 ]. In the case of bones, different polymers have been used for their consolidation, for instance, poly(vinyl acetal), poly(vinyl butyral) and Paraloid B72 [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques of consolidation, such as brushing and immersion in solutions, have been utilized for the restoration of historical artefacts in the past [ 5 , 27 , 28 ]. The advantage of immersion is that usually higher penetration depths are achieved; however, this treatment is in general only convenient for small specimens.…”
Section: Introductionmentioning
confidence: 99%